Effect of roughage on rumen microbiota composition in the efficient feed converter and sturdy Indian Jaffrabadi buffalo (Bubalus bubalis). (December 2015) - Nathani, Neelam; Patel, Amrutlal; Mootapally, Chandra Shekar; Reddy, Bhaskar; Shah, Shailesh; Lunagaria, Pravin; Kothari, Ramesh; Joshi, Chaitanya
Abstract Background The rumen microbiota functions as an effective system for conversion of dietary feed to microbial proteins and volatile fatty acids. In the present study, metagenomic approach was applied to elucidate the buffalo rumen microbiome of Jaffrabadi buffalo adapted to varied dietary treatments with the hypothesis that the microbial diversity and subsequent in the functional capacity will alter with diet change and enhance our knowledge of effect of microbe on host physiology. Eight adult animals were gradually adapted to an increasing roughage diet (4 animals each with green and dry roughage) containing 50:50 (J1), 75:25 (J2) and 100:0 (J3) roughage to concentrate proportion for 6 weeks. Metagenomic sequences of solid (fiber adherent microbiota) and liquid (fiber free microbiota) fractions obtained using Ion Torrent PGM platform were analyzed using MG-RAST server and CAZymes approach. Results Taxonomic analysis revealed thatBacteroidetes was the most abundant phylum followed byFirmicutes, Fibrobacter andProteobacteria . Functional analysis revealed protein (25-30 %) and carbohydrate (15-20 %) metabolism as the dominant categories. Principal component analysis demonstrated that roughage proportion, fraction of rumen and type of forage affected rumen microbiome at taxonomic as well as functional level. Rumen metabolite study revealed that rumen fluid nitrogen content reduced in high roughage diet fed animals and pathway analysis showed reduction in the genes coding enzymes involved in methanogenesis pathway. CAZyme annotation revealed the abundance of genes encoding glycoside hydrolases (GH), with the GH3 family most abundant followed by GH2 and GH13 in all samples. Conclusions Results reveals that high roughage diet feed improved microbial protein synthesis and reduces methane emission. CAZyme analysis indicated the importance of microbiome in feed component digestion for fulfilling energy requirements of the host. The findings help determine the role of rumen microbes in plant polysaccharide breakdown and in developing strategies to maximize productivity in ruminants.